ASSERTIVE BEHAVIOR AND ITS APPLICATION BY ISLAMIC EDUCATION TEACHER IN THE ASSESSMENT OF STUDENT LEARNING OUTCOMES - Huda, Husna Nuur (Universitas Islam Negeri Antasari Banajarmasin, 2020)
This study aimed to find out the application of assertive behavior by the teacher of Islamic Education Studies and to determine the results of the application in improving students? achievement in SMPN 1 Godean. This research is a descriptive qualitative field research. The data collection methods were observation, documentation and interview. Furthermore, the data analysis were using the model of Miles and Huberman which are data reduction, data presentation, and drawing conclusions. The results of this study indicated that the behavior of Islamic Education Studies teacher is able to express the feelings well, sometimes expressed thoughts and beliefs openly and able to maintain the personal rights. Based on those 3 components and 4 characteristics of assertive behavior, the teacher applied 2 components and 3 characteristics of assertive behavior. Thus, the results of the application of Islamic Education Studies teacher's assertive behavior made students in learning the subject were more contented and enthusiastic so that this has an effect on students? achievement, as evidenced by the students? high scores on final test which have an average value above the Minimum Standard Criteria (KKM).